Development of Mind Mapping Media to Teach English Speaking Skill: English - Ferdi Putra; Siti Rofi'ah; Istina Atul Makrifah (Prodi Tadris Bahasa Inggris, 2023)
The objective of the study is to determine processes. and outcomes of using mind mapping to teach English speaking skills for explaining text content in MA Ma'arif Ponggok eleventh grade. Students study a variety of topics at school, including languages. English is one of the languages that students learn at school. The utilization of media is one of the most effective strategies to aid student learning. The ADDIE paradigm is used in this form of study, known as study and Development (R&D). Data for this research were collected by observation, interviews, and a questionnaire. The researcher obtains a score for validating instruments, media, and materials. The instrument validation score is 82.5%, which means